Theory and application of explicitly correlated Gaussians - Mitroy, Jim; Bubin, Sergiy; Horiuchi, Wataru; Suzuki, Yasuyuki; Adamowicz, Ludwik; Cencek, Wojciech; Szalewicz, Krzysztof; Komasa, Jacek; Blume, D.; Varga, Ka´lma´n (My University, 2013)
The variational method complemented with the use of explicitly correlated Gaussian basis functions is one of the most powerful approaches currently used for calculating the properties of few-body systems. Despite its conceptual simplicity, the method offers great flexibility, high accuracy, and can be used to study diverse quantum systems, ranging from small atoms and molecules to light nuclei, hadrons, quantum dots, and Efimov systems. The basic theoretical foundations are discussed, recent advances in the applications of explicitly correlated Gaussians in physics and chemistry are reviewed, and the strengths and weaknesses of the explicitly correlated Gaussians approach are compared with other few-body techniques
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; explicitly correlated Gaussians